Comparison of 12-cm versus 6-cm long peripheral catheters in patients with difficult intravenous access (DIVA) - Pavelková, Kateřina; Lisova, Katerina; Blahova, Petra; Mokra, Dana; Hloch, Ondrej; Charvat, Jiri (The journal of vascular access, 2022)
BACKGROUND: Long peripheral catheter is 6-15 cm long vascular device. The aim of the study was to compare the frequency of complications of two types of long peripheral catheters with different length inserted in DIVA patients. METHODS: Under ultrasound navigation 2.7F 6.4 cm or 4Fr 12 cm long peripheral catheter was inserted. Complications of both long peripheral catheters were prospectively observed and their relationship to the patient's age, gender, selected vein, number of punctures and Barthel score system was evaluated. RESULTS: Ninety-three 12 cm and fifty-five 6.4 cm long peripheral catheters were inserted. Median of dwelling time was 8 days for 6.4 cm and 9 days for 12 cm long peripheral catheter. There were 17 (26%) complications in 6.4 cm (38/1000 catheter days) and 15 (16%) in 12 cm catheter (17/1000 catheter days), p = 0.04. The complications of both peripheral catheters were not associated with the age of patients, gender, number of punctures and selected vein for insertion. Unlike 12 cm catheter, the complications of 6.4 cm long peripheral catheter were significantly associated with the result of Barthel scoring system (p = 0.003). CONCLUSION: The frequency of complications was more common with 6,4 cm than with 12 cm catheter.
Keywords: Humans; Catheters; Catheters, Indwelling; Punctures; lidé; punkce; Administration, Intravenous; Catheterization, Peripheral; katétry; Ultrasonography; ultrasonografie; zaváděcí katétry; periferní katetrizace; intravenózní podání